STRENGTHENING THE LEARNING MODEL OF THE ASATIDZ MADRASAH DINIYAH AT “PONDOK PESANTREN AL ASROR” SEMARANG CITY - Nurkhin, Ahmad; Martono, S; Muhsin, Muhsin; Kardoyo, Kardoyo; Kusumantoro, Kusumantoro; Mukhibad, Hasan (Universitas Negeri Semarang, 2021)
Madrasah Diniyah (Madin) is one of the applications of Islamic education in pesantren huts. Madin must be managed properly to produce learning quality that can improve santri competence. Asatidz council should be given sufficient provision in implementing learning models, classroom mastery, and learning media development. The problems experienced by partners have been the basis for the FE UNNES community service team to provide solutions in strengthening the learning model of the Madin Al Asror asatidz board held in the neighbourhood of As Salafy Al Asror boarding school, Patemon Semarang. Community service activities have been held on Saturday, July 24, 2021, in the hall room of MA Al Asror. The event was attended by 40 teachers madin Al Asror. The caretaker of Pondok Pesantren As Salafy Al Aror, KH Al Mamnukhin Kholid gave a speech and officially opened the event and delivered a certificate of activity participation to participants. The speakers of the activities are experts in education and development of learning media, Ardhi Prabowo, M.Pd. and Ahmad Nurkhin, S.Pd., M.Si. The model of the implementation of devotional activities is interactive lectures, group discussions and group assignments. Participants follow the exposure of the source and continued by making the learning media in groups according to their needs. Participants presented products made and speakers conducted discussions with other participants and madin managers. Participants are very enthusiastic to participate in devotional activities. Madrasah Diniyah (Madin) merupakan salah satu aplikasi pendidikan Islam di pondok pesantren. Madin harus dikelola dengan baik agar menghasilkan kualitas pembelajaran yang mampu meningkatkan kompetensi santri. Dewan asatidz sudah seharusnya diberikan bekal yang cukup dalam menerapkan model pembelajaran, penguasaan kelas, dan pengembangan media pembelajaran. Permasalahan yang dialami mitra selama ini menjadi dasar bagi tim pengabdian kepada masyarakat FE UNNES untuk memberikan solusi dalam penguatan model pembelajaran dewan asatidz Madin Al Asror yang diselenggarakan di lingkungan pondok pesantren As Salafy Al Asror, Patemon Semarang. Kegiatan pengabdian kepada masyarakat telah dilaksanakan pada hari Sabtu, 24 Juli 2021 di ruang Aula MA Al Asror. Kegiatan diikuti 40 guru madin Al Asror. Pengasuh Pondok Pesantren As Salafy Al Aror, KH Al Mamnukhin Kholid memberikan sambutan dan membuka acara secara resmi dan menyampaikan sertifikat partisipasi kegiatan kepada peserta. Narasumber kegiatan adalah pakar Pendidikan dan pengembangan media pembelajaran, Ardhi Prabowo, M.Pd. dan Ahmad Nurkhin, S.Pd., M.Si. Model pelaksanaan kegiatan pengabdian adalah ceramah interaktif, diskusi kelompok dan penugasan kelompok. Peserta mengikuti paparan narasumber dan dilanjutkan dengan membuat media pembelajaran secara berkelompok sesuai dengan kebutuhan. Peserta menyajikan produk yang dibuat dan narasumber melakukan pembahasan bersama peserta lain dan pengurus madin. Peserta sangat antusias mengikuti kegiatan pengabdian.